2018
DOI: 10.2147/cmar.s170160
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation with systemic chemotherapy in the treatment of colorectal cancer liver metastasis: a 10-year single-center study

Abstract: ObjectiveTo retrospectively evaluate the long-term efficacy and safety of radiofrequency ablation (RFA) with systemic chemotherapy (CT) in treatment of solitary liver metastasis after surgery for colorectal cancer (CRC).MethodsThis single-center study was conducted at the Hunan Provincial Cancer Hospital from June 2006 to December 2015 with median follow-up time of 26 months. Percutaneous ultrasound-guided RFA was carried out on eligible patients with solitary liver metastasis after surgery for CRC. After a we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Several previous studies of patients with CRC liver metastasis have reported improved survival (37–45 months) when systemic chemotherapy was combined with local interventions, but outcomes were different in the literature review. Shuangyan et al retrospectively evaluated the long-term survival of 109 CRC patients with liver metastasis treated by RFA plus systemic chemotherapy in China and demonstrated survival outcomes similar to those reported here: (1) median survival of 39 months and (2) 1-year, 3-year, and 5-year survival rates of 92.3%; 50.7%, and 41.6%, respectively [ 14 ]. Rues et al reported the results of a randomized phase II study (EORTC 40004) characterizing RFA combined with systemic chemotherapy for unresectable colorectal liver metastasis.…”
Section: Discussionsupporting
confidence: 64%
“…Several previous studies of patients with CRC liver metastasis have reported improved survival (37–45 months) when systemic chemotherapy was combined with local interventions, but outcomes were different in the literature review. Shuangyan et al retrospectively evaluated the long-term survival of 109 CRC patients with liver metastasis treated by RFA plus systemic chemotherapy in China and demonstrated survival outcomes similar to those reported here: (1) median survival of 39 months and (2) 1-year, 3-year, and 5-year survival rates of 92.3%; 50.7%, and 41.6%, respectively [ 14 ]. Rues et al reported the results of a randomized phase II study (EORTC 40004) characterizing RFA combined with systemic chemotherapy for unresectable colorectal liver metastasis.…”
Section: Discussionsupporting
confidence: 64%
“…affected by the synergistic effect of chemotherapy and RFA, which has been demonstrated in animal experiments (31,32) and in RFA for CRC liver metastases (33).…”
Section: Discussionmentioning
confidence: 87%
“…Available data on the prognostic impact of the CLM hemi-liver location is insufficient, despite many small series reporting poorer prognoses. [25][26][27] The mechanisms of metastatic cancer cell dissemination and implantation are unclear, and no indisputable conclusions can be drawn based on the current knowledge.…”
Section: Left-sided S-clm and Kras Mutationmentioning
confidence: 99%